Leptin stimulates the proliferation of human colon cancer cells in vitro but does not promote the growth of colon cancer xenografts in nude mice or intestinal tumorigenesis in ApcMin/+ mice. Issue 8 (27th April 2005) - Aparicio, T; Kotelevets, L; Tsocas, A; Laigneau, J-P; Sobhani, I; Chastre, E; Lehy, T
Abstract : Background and aims: Leptin, the product of the ob gene, has been suggested to increase the risk of colon cancer. However, we have shown that although leptin stimulates epithelial cell proliferation it reduces the development of carcinogen induced preneoplastic lesions in the rat colon. Here, we explored the effect of leptin in vitro on proliferation of human colon cancer cells, and in vivo on the growth of HT-29 xenografts in nude mice and the development of intestinal tumours in Apc Min /+ mice. Methods: Proliferation of HT-29, LoVo, Caco2, and SW 480 cells was assessed in the absence or presence of leptin (20–500 ng/ml) by 3 H-thymidine incorporation and cell count. Leptin (800 µg/kg/day) or its vehicle was delivered for four weeks to nude mice, inoculated with HT-29 cells on day 0, and for six weeks to Apc Min /+ mice. Results: Leptin dose dependently stimulated cell DNA synthesis and growth in all cell lines. In nude mice, leptin caused a 4.3-fold increase in plasma leptin levels compared with pair fed controls. This hyperleptinaemia, despite leptin receptor expression in tumours, did not induce significant variation in tumour volume or weight. Tumour Ki-67 index was even inhibited. In leptin treated Apc Min /+ mice, a 2.4-fold increase in plasma leptin levels did not modify the number, size, or distribution of intestinal adenomas compared with pair fed controls. Conclusions: Leptin acts as a growth factor on colon cancer cells in vitro but does not promote tumour growth in vivo in the two models tested. These findings do not support a pivotal role for hyperleptinaemia in intestinal carcinogenesis.